Novel Design of Peptides to Reverse the Anticoagulant Activities of Heparin and other Glycosaminoglycans - Schick, Barbara P.; Gradowski, Joel F.; San Antonio, James D.; Martinez, Jose (Thrombosis and Haemostasis, 2001)
Patients undergoing anticoagulation with unfractionated heparin, low molecular weight heparin, or danaparoid may experience excess bleeding which requires reversal of the anticoagulant agent. Protamine is at present the only agent available for reversal of unfractionated heparin. Protamine is not effective in patients who have received low molecular weight heparin or danaparoid. We have developed a series of peptides based on consensus heparin binding sequences (Verrecchio et al., J Biol Chem 2000; 275: 7701-7707) that are capable of neutralizing the anti-thrombin activity of unfractionated heparin in vitro, the antifactor Xa activity of unfractionated heparin, Enoxaparin (Lovenox) and danaparoid (Orgaran) in vitro and the anti-Factor Xa activity of Enoxaparin in vivo in rats. These peptides may serve as alternatives for Protamine reversal of UFH and may be useful for neutralization of enoxaparin and danaparoid in humans.
Keywords: Peptide; heparin; low molecular weight heparin; Lovenox; danaparoid; Orgaran; reversal of anticoagulation; serglycin